ä½¿ç”¨å—å¡æé«˜å¤åŠ¡æ‹‰é›…é«˜ä¸å››æ ¡ä¸‰å¹´çº§å¦ç”Ÿè®¤è¯»æ±‰å—èƒ½åŠ› - Kurniati, Fitri; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Chinese characters is a written form a Chinese language. In it’s proces, Chinese character is the most important element in Chinese language as foreign language. Student who has just begun learning in Chinese character will have some difficulties recognizing, remembering,reading and writing the Chinese character as first. In activity of teaching and learning, there are some student who could read the characters but not the meaning, there are fews who knows the character but do not know how to read it. Therefore ti save this problem, the learner can usea learning method such as Chinese logograph card to help them to recognize the character.The purpose of this learning is to imply if the logograph cards method could improve the ability of learning the Chinese character. Therefore the writer has chosen SMA Negeri 04 Kuburaya kelas XII as the experiment object. Based on the experiment, this method has reduced the problem, from 52% of errors in the beginning becomes 10% in the end of the rest. It as well proses that the logograph card really help in increasing the students ability to remember the character. Keyword : Chinese, Character, Card Learning Media